ANALISIS PENGELOLAAN ANGGARAN BELANJA DAN PENDAPATAN PADA DESA REKIMAI JAYA KECAMATAN SEMENDE DARAT TENGAH KABUPATEN MUARA ENIM PROVINSI SUMATERA SELATAN - Ayu Febrianty Rahma; Usdeldi Usdeldi; Saijun Saijun (Jurnal Kajian dan Penalaran Ilmu Manajemen, 2023)
This study aims to determine the management of the expenditure and income budget in Rekimai Jaya Village, Semende Darat District, Muara Enim Regency during 2019-2021. This type of research used in this research is descriptive qualitative research that tends to use inductive analysis. The data collection technique that was carried out was by observing the field office of the Rekimai Jaya Village, also conducting interviews with the head of the Rekimai Jaya Village, village officials and also the people of the Rekimai Jaya Village. Besides that, documentation techniques are also carried out, namely by collecting data related to the APBDes and other influential documents. From this study it proves that the preparation of the APBDes in Rekimai Jaya Village is good because it has carried out transparency such as placing billboards or banners related to its management.